Community Empowerment through Freshwater Fish Processing (Toman) as a Result of Processed Creative Communities in Kumba Village, Jagoi Babang District, Bengkayang Regency - Emi Sulistri; Lili Yanti; Sri Mulyani; Nurhayati Nurhayati; Sumarli Sumarli; Heru Susanto; Rini Setyowati; Rika Wahyuni; Erdi Guna Utama (STKIP Singkawang, 2019)
Training and mentoring are conducted for Kumba hamlet residents, especially among housewives in Jagoi Babang District. This mentoring program involves the lecturers and students of KKN STKIP Singkawang. A method that is used is the identification of the programs is socialization, training, and mentoring directly resulted in the form of the manufacturing practice of toman fish Abon. Toman fish processing into Abon is one way to utilize the potential of toman fish as a skills program to maximize innovative, creative and economic empowered business opportunities. The results of this socialization activity are students can play an active role in the activities and participants involved in Kumba Village can be understood the material presented. Overall, community empowerment partners can understand and practice material related to how they are created, the benefits, and marketing management. However, more intensive assistance is needed for business management related to business planning and financial management.